Actions taken by dental care providers in relation to COVID-19 - Denia Morales Navarro (Editorial Ciencias Médicas, 2020)
Introduction: The outbreak of coronavirus disease 2019 (COVID-19) has been declared a worldwide public health emergency. Dentists are the health care providers most directly exposed to this condition, since their area of activity is the mouth, a location recognized as the site through which the disease is transmitted. Objective: Clarify some notions about COVID-19 and the measures to be taken to prevent transmission to dental care providers. Main remarks: A single method has not been discovered which meets all the requirements concerning infections associated to medical care. In the struggle against COVID-19 an important role is played by standard precautions, i.e. measures applied to all patients, irrespective of their diagnosis or whether they are known to have an infection or be colonized by a given agent. SARS-CoV-2 is an enveloped virus, a characteristic that makes it more sensitive to the action of disinfectants. General considerations: COVID-19 presents non-specific symptoms, the most common of which are fever, anorexia and dry coughing. Transmission probably occurs by the spread of the virus in the air and by direct contact. Implementation of standard precautions, among which are hand hygiene, the use of personal protection equipment and care for the environment, will lead to a reduction in the chances of contagion and will contribute to control the spread of the disease. It is important for medical care providers, among them dental care professionals, and the public at large to know about this new virus, so that coordinated, timely and effective actions may be taken which will help prevent the occurrence of new cases or bad results in the struggle against this pandemic.